(5n-4)(n-7)=0

Simple and best practice solution for (5n-4)(n-7)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5n-4)(n-7)=0 equation:



(5n-4)(n-7)=0
We multiply parentheses ..
(+5n^2-35n-4n+28)=0
We get rid of parentheses
5n^2-35n-4n+28=0
We add all the numbers together, and all the variables
5n^2-39n+28=0
a = 5; b = -39; c = +28;
Δ = b2-4ac
Δ = -392-4·5·28
Δ = 961
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{961}=31$
$n_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-39)-31}{2*5}=\frac{8}{10} =4/5 $
$n_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-39)+31}{2*5}=\frac{70}{10} =7 $

See similar equations:

| 7(4x+3)=273 | | c-59=5c+9 | | x/3x-5=1/2x+2x | | x/9+2/3=4/9 | | g-10=100 | | (-2/3)x+1/4=(3/5)x-5/6 | | 7y+5(y-2)=26 | | 4(2s-1)=7s=12 | | v+4=(-15) | | a+234=-6a+3 | | 1/4z=22/8 | | 5(x–1)+3x=7(x+1)= | | x/5=12/20x= | | 6x2=18x | | 5n+5=9n+3 | | v+4=|-15| | | 4/3x-3=x+7 | | 11-7(-12n+9)=11+7(11n+1) | | 46-xx=38 | | 5a+17=22 | | 2a+a=25 | | 11-7(12n+9)=11+7(11n+1) | | 4/5=16/z | | 4(2x-1)-x-4=-1 | | 3(x–2)+7=40 | | -1/3x=22 | | 10-2aa=4 | | X+4x+80=180 | | 1/5(x+5/3)=-16/15 | | 0.75x+6=16.5 | | 4n−9=−9 | | 10x-5=40-5x |

Equations solver categories